Breaking Legal and Socio-economic Challenges to Plastic Waste Regulation in Nigeria: Lessons learned from Singapore - Aidonojie, Paul Atagamen; Afolabi, Majekodunmi Toyin; Obieshi, Eregbuonye; Adeyemi-Balogun, Molola Janet; Wakili, Saminu Abacha (Yustisia, 2024)
Plastic, a versatile material derived from synthetic compounds, is widely employed globally due to its durability, cost-effectiveness, and ease of production. However, its improper disposal poses significant environmental threats. Despite concerted efforts, the indiscriminate dumping of plastic waste persists in the country's land and water environments. This study aims to comprehensively explore the legal guidelines and socio-economic initiatives relevant to plastic waste regulation, drawing inspiration from Singapore's successful model. Three hundred and ten questionnaires were also distributed among residents of Nigeria to achieve this objective. The data collected underwent thorough analysis, employing both descriptive and analytical methods. In this context, Singapore stands out as an exemplary model for Nigeria to emulate in addressing the challenges posed by plastic waste. Drawing inspiration from Singapore's successful strategies, It is imperative to meticulously regulate every stage, from production to disposal, to ensure environmental sustainability and minimize the detrimental impact of plastic pollution. The study found the need for more legislative measures in Nigeria to combat the pervasive problem of indiscriminate plastic waste disposal effectively. Also, The government should establish irresponsible plastic waste disposal's environmental and health risks and dumping of plastic waste.